Risk factors for surgical site infection after hysterectomy - Göksever Çelik, Hale; Çelik, Engin; Turan, Gökçe; Seçkin, Kerem Doğa; Gedikbaşı, Ali (The Journal of Infection in Developing Countries, 2017)
Introduction: The aim of the study was to define the clinical and laboratory characteristics of patients who had surgical site infection (SSI) after hysterectomy. Methodology: This study was a retrospective cohort study. The patient data of 840 subjects who had undergone any type of hysterectomy and reported SSI after surgery were obtained from the archives of a tertiary referral center. The different types of hysterectomy procedures performed on these patients included total abdominal hysterectomy (TAH), laparoscopic hysterectomy (LH), and vaginal hysterectomy (VH). In addition, age, body mass index (BMI), preoperative and postoperative blood parameters, gravidity, and parity were also documented. Results: TAH, LH, and VH were performed on 63.2% (n = 531), 21.6% (n = 181), and 15.2% (n = 128) of patients, respectively. Overall, SSIs were observed in 3.7% (n = 31) of all hysterectomy patients. Among them, 4.5% of TAH patients, 1.7% of LH patients, and 3.1% of VH patients had SSIs after the hysterectomy operation. Analysis of the data revealed that the patients with SSIs had significantly higher BMIs, lower preoperative hemoglobin, lower postoperative hemoglobin and hematocrit, and higher postoperative platelet counts compared to patients who did not have any SSIs. Conclusions: High BMI, blood loss during surgery, low hematocrit levels, and resulting anemia increased the incidence of SSI after hysterectomy. Among the different types of hysterectomy, LH was found to be relatively better than TAH and VH in preventing the occurrence of SSI.